English oral communication in public secondary schools in Kazakhstan: understanding its practice and challenges - Kemboja Ismail; Almagul Tuspekova; Rosniah Mustaffa (Penerbit Universiti Kebangsaan Malaysia, 2018)
The teaching of oral communication (OC) has been addressed in different ESL and EFL contexts, though mainly in a university setting. However, it has received little attention in the Central Asian context. This paper will provide preliminary insights into the practice of teaching English OC and the challenges associated with it in public schools in Kazakhstan (KZ), a country in Central Asia. For the pilot study reported here, data was collected from 18 KZ learners from 9 different schools via e-mail interviews. The study was guided by a theoretical model representing three levels of influence on OC practice: micro, meso, and macro. The current OC activities were found to be lacking in spontaneity, too teacher-centred and individual-oriented. At the micro level, emotional constraints were considered to have a greater impact on female students’ oral performance, while limited linguistic repertoire affected male students’ oral production. At the meso level, females found a lack of emotional support from their teachers, while males preferred to have out-of-class help from their friends to practise English. At the macro level, males were found to be more influenced by a wider sociocultural context than females. Firstly, the findings reveal the gap between the actual and preferred OC practices in KZ public schools, which can be further addressed by the stakeholders. Secondly, they illustrate how gender influences the way learners engage in OC activities. And lastly, they underline the importance of examining OC in relation to learners’ self, their social communities and the overarching context that shapes their attitude towards a language.